PENGALAMAN AUDITOR SEBAGAI PEMODERASI PENGARUH TIME BUDGET PRESSURE DAN KOMPLEKSITAS AUDIT PADA KUALITAS AUDIT - Riyandari, Putu Karina; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2017)
Financial statement is necessarily to be audited by the public accountant as the third party outside the company in order to avoid error occurred. Financial statement which has been audited is more credible. The aim of this study is to provide empirical evidence of the time budget pressure and audit complexity effect on audit quality with the auditor’s experiences as the moderating variables. This research took a sample based on non-probability method, using the saturation sampling technique. Therefore, all auditors at KAP in Bali who have been registered in IAPI become the sample. Regression analysis is used as analysis technique with and without the moderating variable. This research find out time budget pressure has negative and significant effect on audit quality, audit complexity has negative and significant effect on audit quality, and the auditor’s experiences are able to moderate and strengthen time budget pressure effect on audit quality.
Keywords: auditor’s experiences, time budget pressure, audit complexity, audit quality